Reorganizing a Medicine Residency Program in Response to the COVID-19 Pandemic in New York. (November 2020) - Manson, Daniel K.; Shen, Sherry; Lavelle, Michael P.; Lumish, Heidi S.; Chong, David H.; De Miguel, Maria H.; Christianer, Kaylan; Burnett, Eric J.; Nickerson, Katherine G.; Chandra, Subani
Abstract : The COVID-19 pandemic has been particularly severe in New York City, resulting in a rapid influx of patients into New York–Presbyterian Hospital/Columbia University Irving Medical Center. The challenges precipitated by this pandemic have required urgent changes to existing models of care. Internal medicine residents are at the forefront of caring for patients with COVID-19, including the critically ill. This article describes the exigent restructuring of the New York–Presbyterian Hospital/Columbia University Internal Medicine Residency Program. Patient care and educational models were fundamentally reconceptualized, which required a transition away from traditional hierarchical team structures and a significant expansion in the program's capacity and flexibility to care for large numbers of patients with disproportionately high levels of critical illness. These changes were made while the residency program maintained the priorities of patient care and safety, resident safety and well-being, open communication, and education. The process of adapting the residency program to the demands of the pandemic was iterative given the unprecedented nature of this crisis. The goal of this article is to share the experiences and lessons learned from this crisis, communicate the solutions that were designed, and inform others who may be facing the prospect of creating similar disaster response measures.